ANALISIS PERANAN PENERIMAAN RETRIBUSI PARIWISATA TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN TANAH LAUT TAHUN 2013-2017 - ANNISA ANNISA; RIZALI RIZALI (PPJP Universitas Lambung Mangkurat, 2019)
The purpose of the research are (1) to find out the role of tourism retribution to Regional Retribution and Original Local Government Income(PAD) in Tanah Laut District during 2013-2017 fiscal year, (2) to know the retribution collection level of effectivenessin Tanah Laut District during 2013-2017 fiscal year, (3) to know the impact of of the tourism development after the result of tourism retribution in Tanah Laut district during 2013-2017 fiscal year, (4) analyze the efforts that must be made by the government of Tanah Laut District on developing tourism objects as one of sources of Original Local Government Income(PAD. The research method used quantitave descriptive analysis using secondary and primary data, through the collection and available data on the Department of Culture and Tourism of Tanah Laut District and related agencies, and also the literature that has to do with this research besides conducting interviews or interviews directly with relevant agencies, administrator, and tourist in Tanah Laut District. The results showed that the average role tourism retribution in Tanah Laut District during 2013-2017 fiscal year was very lacking, which is 5,97% for the average role of the tourism retribution on regional retribution, and 0,27% for the role average tourism retribution on Original Local Government Income (PAD). The calculation of effectiveness level of tourism retribution in Tanah Laut District showed less effective results with average 78,75%. The receipt of tourism retribution in Tanah Laut District has an impact on the development of the tourism objects it self, especially tourism objects that have contibuted to retribution Incomes such as Takisung Beach, Batakan Beach, Swarangan Beach, Batu Lima Beach, Sepeda Air, Kereta Wisata, Tirta Kirana Swimming Pool, Kayangan Mountain, and Bajuin Waterfall. The efforts that must be made by the Tanah Laut Government especially the Tanah Laut Department of Culture and Tourism to develop the tourism sector are organizing attractive tourism events, allocating sufficient funds for the development and management costs of the tourism sector, improving the main facilities and infrastructure in tourism object places, improve human resources espacially for administrator of tourist attractions, socialization to the public and agencies / institutions to support the success of tourism sector, and intensify the promotion of tourism objects.Key Words : Tourism, Tourism Retribution, Original Local Government Income (PAD)